RELEVANSI KOMPETENSI TKRO SMK MUHAMMADIYAH KARANGMOJO DENGAN KOMPETENSI YANG DIBUTUHKAN INDUSTRI: Indonesia, Inggris - Agus Budiman; Rizaldi Isnadar (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2024)
ABSTRACT This study aims to determine: (1) the competence of Automotive Light Vehicle Engineering (TKRO) at SMK Muhammadiyah Karangmojo; (2) the competency needs of the APM business and automotive industry following the TKRO Skills Competency curriculum given by SMK Muhammadiyah Karangmojo; (3) the relevance of the TKRO competencies given at SMK Muhammadiyah Karangmojo to the needs of the business world and the APM automotive industry. This research is descriptive quantitative and qualitative research. The subject of this research is the Head of TKRO Expertise Competence at SMK Muhammadiyah Karangmojo and 5 respondents from 5 DU/DI automotive APMs. Data collection techniques in this study used documentation, questionnaires, and interviews. The data analysis technique in this study used quantitative descriptive analysis with percentages. The results of this study indicate that: (1) competence in the curriculum of SMK Muhammadiyah Karangmojo TKRO expertise competence consists of 256 KD, (2) competencies required by DU/DI automotive APM consist of 238 KD meaning there are several KD that DU/DI APM does not require, and (3) The relevance of the TKRO competencies given at SMK Muhammadiyah Karangmojo to the overall need for DU/DI APM is 82%, with details of 191 (75%) Basic Competencies in the very relevant category, 26 (10%) Basic Competencies in the relevant category, 21 (8%) Basic Competencies in the less relevant category, and 18 (7%) Basic Competencies in the irrelevant category. Keywords: Relevance, Basic Competencies, Automotive Light Vehicle Engineering, the Automotive industries ABSTRAK Penelitian ini bertujuan untuk mengetahui: (1) kompetensi Keahlian Teknik Kendaraan Ringan Otomotif (TKRO) di SMK Muhammadiyah Karangmojo; (2) kompetensi kebutuhan dunia usaha dan industri otomotif APM sesuai kurikulum Kompetensi Keahlian TKRO yang diberikan SMK Muhammadiyah Karangmojo; (3) relevansi kompetensi TKRO yang diberikan di SMK Muhammadiyah Karangmojo dengan kebutuhan dunia usaha dan industri otomotif APM. Penelitian ini merupakan penelitian deskriptif kuantitatif dan kualitatif. Subjek penelitian ini adalah Ketua Kompetensi Keahlian TKRO SMK Muhammadiyah Karangmojo dan 5 responden dari 5 DU/DI otomotif APM. Teknik pengambilan data dalam penelitian ini menggunakan dokumentasi, angket dan wawancara. Teknik analisis data dalam penelitian ini menggunakan analisis deskriptif kuantitatif dengan persentase. Hasil penelitian ini menunjukkan bahwa: (1) kompetensi pada kurikulum SMK Muhammadiyah Karangmojo kompetensi keahlian TKRO terdiri dari 256 KD, (2) kompetensi yang dibutuhkan DU/DI otomotif APM terdiri dari 238 KD artinya terdapat beberapa KD yang tidak dibutuhkan oleh DU/DI APM, dan (3) Relevansi kompetensi TKRO yang diberikan di SMK Muhammadiyah Karangmojo dengan kebutuhan DU/DI APM secara keseluruhan sebesar 82%, dengan rincian 191 (75%) Kompetensi Dasar dalam kategori sangat relevan, 26 (10%) Kompetensi Dasar dalam kategori relevan, 21 (8%) Kompetensi Dasar dalam kategori kurang relevan, dan 18 (7%) Kompetensi Dasar dalam kategori tidak relevan. Kata kunci: Relevansi, Kompetensi di SMK, Kompetensi yang dibutuhkan DU/DI APM, TKRO SMK Muhammadiyah Karangmojo.